Impact of the Swedish National Stroke Campaign on stroke awareness. (31st May 2017) - Nordanstig, A.; Asplund, K.; Norrving, B.; Wahlgren, N.; Wester, P.; Rosengren, L.
Abstract : Background: Time delay from stroke onset to arrival in hospital is an important obstacle to widespread reperfusion therapy. To increase knowledge about stroke, and potentially decrease this delay, a 27‐month national public information campaign was carried out in Sweden. Aims: To assess the effects of a national stroke campaign in Sweden. Methods: The variables used to measure campaign effects were knowledge of the AKUT test [a Swedish equivalent of the FAST (Face‐Arm‐Speech‐Time)] test and intent to call 112 (emergency telephone number) . Telephone interviews were carried out with 1500 randomly selected people in Sweden at eight points in time: before, three times during, immediately after, and nine, 13 and 21 months after the campaign. Results: Before the campaign, 4% could recall the meaning of some or all keywords in the AKUT test, compared with 23% during and directly after the campaign, and 14% 21 months later. Corresponding figures were 15%, 51%, and 50% for those remembering the term AKUT and 65%, 76%, and 73% for intent to call 112 when observing or experiencing stroke symptoms. During the course of the campaign, improvement of stroke knowledge was similar among men and women, but the absolute level of knowledge for both items was higher for women at all time points. Conclusion: The nationwide campaign substantially increased knowledge about the AKUT test and intention to call 112 when experiencing or observing stroke symptoms, but knowledge declined post‐intervention. Repeated public information therefore appears essential to sustain knowledge gains.